Factors influencing species reintroduction success - Gemma Harding; Richard A. Griffiths; Simon A. Black (Biodiversity and Conservation, 2025)
Conservation reintroductions are widespread in species conservation but evaluation of their success, and particularly the reporting of failures is lacking. Here we evaluate aspects of species reintroduction that influence success and how conservation practitioners measure success. We analysed trends and reasons for perceived failure and success across 341 documented reintroduction case studies from across the globe. Reintroductions in Africa had lower scores for success compared to East Europe, North & Central Asia; fish had higher scores than invertebrates; and government and non-government organisations scored projects as more successful than did zoos or aquaria. Goals and Indicators do not appear to influence the success score, although too many goals may have a negative influence on success. Qualitative analysis of the reasons for failure and success showed that activities linked to Partnerships & Support (e.g. community support, government partnerships) were the most regularly cited reason for success, and Habitat & Release site (e.g. poor habitat connectivity, lack of suitable release sites) were the most frequently cited reason linked to failure, or failed elements. Current conservation efforts continue to comprise a disproportionately high number of reintroductions for mammals and birds compared to other taxa, and the number of reintroductions in developed countries outweigh those of developing countries.